Study on Measuring and Forecasting of Fully Mechanized Working Face Roof Pressure System - Yong Zhang; XueQiang Yang; ZengXin Wang (Institute of Advanced Engineering and Science, 2014)
China is one of the largest coal producer and consumer countries in the world. However, due to the complexity of coal resources, storage conditions, geological disaster-prone coal mines, it is also a coal mine accidents multiple country, coal mine accidents and deaths of China accounted to about 80% total of the world. In the coal mine accident occurred, roof accident has accounted for around 40%,such as the roof collapsed, slipped, deformation, obstruction and so on. So the monitor and early warning of roof is particularly important. State of motion is closely related to mine roof pressure. Roof support pressure or resistance can be measured by the pressure sensor. The data send to the ring Ethernet underground and transmit to the monitoring center of ground. Through information analysis processing, it could provide real-time data and early warning, alarm information. Applied time series theory analysis and forecasting future pressure changes, can master the roof movement trends and regularity, guide safe production. So the decisions have some practical significance. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4779